Pertumbuhan dan Hasil Beberapa Klon Ubi Jalar (Ipomoea batatas L.) di Dataran Menengah Saree, Kabupaten Aceh Besar - Mardhiah Hayati; Nurhayati Nurhayati; Ainun Marliah; Munawar Khalil (Jurnal Floratek, 2016)
Growth and Yields Performance of Several Clones of Sweet Potato (Ipomoea batatas L.) at Medium Highland of Saree, District of Aceh Besar ABSTRACT. The purpose of this study is to obtain an adaptable clones with high productivity at the medium highland of Saree, in the district of Aceh Besar. This research was conducted at experimental station of The Agriculture Mentor Academy at Saree, Aceh Besar with the altitude of 520 m above sea level, from February to July 2015. The study used a non factorial Randomized Block Design. The factors being tested are 12 types of potato clone, where nine were obtain from the International Potato Center of South East Asia (CIP-SEA) Bogor, West Java (CIP-440137, CIP-AC, CIP-B19, CIP-286, CI-287, CIP-GA, SARI, CIP-W, CIP-W104) and 3 local clones (White Saree, Yellow Saree, Bener Meriah). The results show that clones have a very significant impact on the percentage of life at 3 weeks after planting (WAP), long vines (4 and 6 WAP) and biomass dry weight, and significantly impact on the number of vines. The best plant growth is found on CIP-B19 and CIP -W104, while highest yields achieved by CIP- GA and CIP-W104.